Novel Integration of Administrative Pharmacy Residents in a Management Course - James Ford; Katherine Rotzenberg; David Mott (University of Minnesota Libraries Publishing, 2021)
Background: Management skills are an essential component of a pharmacy graduate's abilities for successful practice.  Although pharmacy education standards require that students have a working knowledge of management principles, students often do not see the value in management and business courses.  One innovative approach is restructuring course content using case examples and real-world experiences to improve student understanding of finance and management principles. Innovation: Two specific changes were implemented in a second year (P2) management and finance course to improve the relevance of business principles.  Course content was organized around current pharmacy service cases from a variety of practice settings and supported by the value of problem-based learning.  Post-graduate year 1 (PGY-1) administrative pharmacy residents were engaged as course teaching assistants (TAs) who brought real-world experiences into the class.  An analysis of pre- and post-course voluntary surveys, course evaluations, and TA evaluations assessed the impact of the course redesign. Findings: The course redesign achieved its intended goal of improving student-perceived course relevance.  This was shown through statistically significant improvements in course evaluations that were intended to measure student perception of pharmacy management and its relevance in their future career.  Student completed TA evaluations showed that those who reported their TA shared real-world applications had higher confidence in applying course concepts and greater understanding of course materials. Conclusions: Administrative pharmacy residents were successfully integrated into a pharmacy management course redesign, resulting in improved student perceptions of course relevance.